Marketing Strategy Analysis on Sales of Wawan Bottle Waste in Pusakanegara District, Subang - Yadi, Ramidi; Nugraha, Riki Ahmad; Setiabudi, Firman; Mulyani, Sri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the marketing strategy implemented by Limbah Botol Wawan in increasing sales in Pusakanegara Subang District, as well as to analyze the advantages and disadvantages of this strategy. Methods used in study This is descriptive qualitative . The results of the study indicate that the marketing mix elements of product, price, place, and promotion play an important role in increasing sales. Diverse and high-quality products are the main attraction, while competitive pricing and discount promotions contribute significantly to purchasing interest. Although the strategic location makes it easy for consumers to access, challenges such as limited delivery fleets and tight price competition must be overcome. The use of advertising , social media, and personal selling have also proven effective in increasing product visibility. Recommendations for management include increasing the delivery fleet, adjusting prices with competitors, and improving the quality of personal selling to maintain and increase market share. This study provides important insights for the development of MSME marketing strategies in the distribution sector.